Elevated autoimmunity in residents living near abandoned uranium mine sites on the Navajo Nation. (May 2019) - Erdei, Esther; Shuey, Chris; Pacheco, Bernadette; Cajero, Miranda; Lewis, Johnnye; Rubin, Robert L.
Abstract: Specific autoantibodies were assessed among residents of the Navajo Nation in New Mexico chronically exposed to metal mixtures from uranium mine wastes and in drinking water supplies. Age and the extent of exposure to legacy waste from 100 abandoned uranium mine and mill sites were associated with antibodies to denatured DNA, previously known to be an early indicator of medication-induced autoimmunity. Surprisingly, autoantibodies to native DNA and/or chromatin were also linked to environmental exposure, specifically uranium consumption through drinking water for both men and women, while urinary arsenic was negatively associated with these autoantibodies in women. These findings suggest that contaminants derived from uranium mine waste enhanced development of autoantibodies in some individuals, while arsenic may be globally immunosuppressive with gender-specific effects. Specific autoantibodies may be a sensitive indicator of immune perturbation by environmental toxicants, an adverse effect not considered in current drinking water standards or regulatory risk assessment evaluations. Highlights: Environmental exposure to uranium mines and mill sites and serum autoantibodies were assessed in Navajo Nation residents. Life-long exposure was associated with anti-denatured DNA antibodies, especially in men. Anti-native DNA/-chromatin autoantibodies were linked to uranium consumption through drinking water. Arsenic consumption through water and urinary arsenic were negative predictors of autoantibodies. Specific autoantibodies may be of value for monitoring immune-perturbing effects of environmental toxicants.